EFEKTIVITAS PENERAPAN METODE SOROGAN KITAB MATAN AL-GHOYAH WATTAQRIB (FATHUL QORIB ) PENGARANG ABI SYUJA’ AHMAD BIN HUSAIN AL-ASHFIHANI - Eliyawati; Widiyati, Evita (EL-Islam, 2022)
Abstract: The results of this study indicate that first, the sorogan method at Pondok Putri Pesantren Tebuireng Jombang is very effective because with the sorogan method for students at Wisma PKK (Program Pedalaman Kitab Kuning) it is easier for students to learn and understand the book and it is easier to understand the nahwu and its shorof. Because every sorogan meeting they must be able to understand the contents of the book and the science of nahwu shorofnya. Second, the sorogan method at Pondok Putri Pesantren Tebuireng Jombang, students very effectively apply the sorogan method. Santri gather in groups, listen, listen to readings from an Ustadz or Ustadzah sitting in front of the students who listen to the contents of the book read by Ustadz or Ustadzah. Third, the positive impact on the sorogan method is that students are required to understand the Nahwu and Sorof material and the contents of the book and from there students understand the contents of the book and the knowledge of nahwu and shorof. Santri are very effective when the sorogan activity takes place and they understand the contents of the book and the nahwu shorof in the book. The negative impact in the sorogan method is that students only study one book, namely Fathul Qorib not studying books other than the Matan Al-Ghoyah Wattaqrib (Fathul Qorib).